Influence of selected dosages of plastic microparticles on the porcine fecal microbiome - Ismena Gałęcka; Andrzej Rychlik; Jarosław Całka (Scientific Reports)
Abstract Studies conducted so far have shown that nano- and microplastic may disturb the intestinal microenvironment by interacting with the intestinal epithelium and the gut microbiota. Depending on the research model used, the effect on the microbiome is different—an increase or decrease in selected taxa resulting in the development of dysbiosis. Dysbiosis may be associated with intestinal inflammation, development of mental disorders or diabetes. The aim of the study was to analyze the intestinal microbiome in 15 gilts divided into 3 research groups (n = 5; control group, receiving micropartices at a dose 0.1 g/day (LD) and 1 g/day (HD)). Feaces were collected before and after 28 days of exposure to PET microplastics. The analysis of the intestinal microbiome was performed using next-generation sequencing. Alpha and beta diversity indices were compared, showing, that repetition affected only the abundance indices in the control and LD groups, but not in the HD group. The relationships between the number of reads at the phylum, genus and species level and the microplastic dose were calculated using statistical methods (r-Pearson correlation, generalized regression model, analysis of variance). The statistical analysis revealed, that populations of Family XIII AD3011 group, Coprococcus, V9D2013 group, UCG-010 and Sphaerochaeta increased with increasing MP-PET dose. The above-mentioned taxa are mainly responsible for the production of short-chain fatty acids (SCFA). It may be assumed, that SCFA are one of the mechanisms involved in the response to oral exposure to MP-PET.